Biogeografia e efeitos da fragmentação florestal sobre aves na região da Planície Alagável do Alto Rio Paraná, entre os estados de Mato Grosso do Sul e Paraná, Brasil. - Lopes, Edson Varga (2009)
This study analyzed the forest birds distribution and sensitivity to forest fragmentation in the Upper Paraná River Floodplain (PAAP) region by comparing the avifauna of the two margins (Mato Grosso do Sul; MS and Paraná; PR) of the Paraná River. The landscapes of two margins are distinct because PAAP is located near the boundaries of both Central South America (CSA) and Atlantic Forest (ATL) biogeographic zone, with each margin being represented by one zone and due to the presence of a floodplain only at the MS margin. The communities were similar in structural parameters, but there were low qualitative and quantitative similarities between the margins, possibly due to the influence of the biogeographic zones; several species related either to CSA or ATL zones occurred exclusively, or were more abundant, at the margin were they were expected to occur. The avifaunal sensitivity to forest fragmentation varied between the margins, with greater proportion of bird species not sensitive at the MS margin. In addition, the degree of sensitivity of 30% of the species recorded at the two margins and the sensitivity of some functional groups with characteristics less affected negatively by fragmentation vary between the margins. The sensitivity of the species related to either the CSA or ATL zone was distinct, once that none of the species related to the CSA zone at MS margin were considered sensitive, while species related to the ATL zone had greater proportion of sensitive species at both margins. Overall, this study suggests a transition between the CSA and ATL avifauna in the PAAP region and recommends that conservation strategies should consider such regional feature since the sensitivity of functional groups or species can vary between landscapes.